2008
DOI: 10.1103/physrevlett.101.207206
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Understanding of Negative Magnetization in Cu, Mn, and Fe Based Prussian Blue Analogues

Abstract: A crossover of the field-cooled magnetization from positive to negative has been observed below the magnetic ordering temperature (17.9 K) in a multimetal Prussian Blue analogue (PBA), Cu_{0.73}Mn_{0.77}[Fe(CN)_{6}].zH_{2}O. The reverse Monte Carlo (RMC) modeling (using the program RMCPOW) has been used to derive the various scattering contributions (e.g., nuclear diffuse, nuclear Bragg, magnetic diffuse, and magnetic Bragg) from the observed neutron diffraction patterns. The RMC analysis combined with the Rie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 23 publications
0
67
0
Order By: Relevance
“…Negative magnetization was observed more than five decades ago in spinel-like Co 2 VO 4 [60], and more recently in natural ferrites such as magnetite and maghemite [61] [67], Cu, Mn and Fe based prussian blue analogues [42], Co 2 CrAl type Heusler alloy, inorganic compounds [68] and CuFe 2 O 4 thin film [69]. A number of mechanisms and new models have been proposed to explain the phenomenon of negative magnetization [64].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Negative magnetization was observed more than five decades ago in spinel-like Co 2 VO 4 [60], and more recently in natural ferrites such as magnetite and maghemite [61] [67], Cu, Mn and Fe based prussian blue analogues [42], Co 2 CrAl type Heusler alloy, inorganic compounds [68] and CuFe 2 O 4 thin film [69]. A number of mechanisms and new models have been proposed to explain the phenomenon of negative magnetization [64].…”
Section: Resultsmentioning
confidence: 97%
“…A microscopic understanding of this phenomenon can be effectively utilized to tailor the magnetic properties for various applications. This would facilities the design of various magnetic memories, thermo magnetic switches and magnetic cooling/heating devices [42]. The authors have observed a crossover of the ZFC magnetization from positive to negative for the CuAl 0.6 Fe 1.4 O 4 (x = 0.6) composition, below their magnetic ordering temperature.…”
Section: Introductionmentioning
confidence: 98%
“…They exhibit all the phenomena observed in conventional transition-metal and rare earth-based magnets, and more, by exhibiting liquid crystallinity, chirality, low density, solubility, spin-crossover (Krober et al 1993), negative magnetization (Mathoniere et al 1994;Chavan et al 1996;Kumar et al 2008), photoinduced magnetization/switching due to their coloured nature Sastry et al 1999;Pejakovic et al 2002), and possibility of modulation of their properties electrochemically, all of which are arising from their characteristic molecular nature. In this context, an exciting development is the fabrication of a tri-functional phenalenyl-based neutral radical, by Itkis et al (2002), which exhibits magneto-opto-electronic bistability with hysteresis loops centred near 335 K, thus opening the possibility for new type of electronic devices, where multiple physical channels can be used for writing, reading, and transferring information.…”
Section: Current Scenario and Future Perspectivesmentioning
confidence: 98%
“…These materials possess very high spin state and large magnetic anisotropy. These materials are now known for their potential technological applications [2]. These include information processing, data storage, quantum computing, spintronics, biomedical applications (like MRI contrast agents), magnetic refrigeration, etc.…”
Section: Introductionmentioning
confidence: 99%